Simvastatin-Mediated Nrf2 Activation Induces Fetal Hemoglobin and Antioxidant Enzyme Expression to Ameliorate the Phenotype of Sickle Cell Disease - Caixia Xi; Chithra Palani; Mayuko Takezaki; Huidong Shi; Anatolij Horuzsko; Betty S. Pace; Xingguo Zhu (MDPI AG, 2024)
Sickle cell disease (SCD) is a pathophysiological condition of chronic hemolysis, oxidative stress, and elevated inflammation. The transcription factor Nrf2 is a master regulator of oxidative stress. Here, we report that the FDA-approved oral agent simvastatin, an inhibitor of hydroxymethyl-glutaryl coenzyme A reductase, significantly activates the expression of Nrf2 and antioxidant enzymes. Simvastatin also induces fetal hemoglobin expression in SCD patient primary erythroid progenitors and a transgenic mouse model. Simvastatin alleviates SCD symptoms by decreasing hemoglobin S sickling, oxidative stress, and inflammatory stress in erythroblasts. Particularly, simvastatin increases cellular levels of cystine, the precursor for the biosynthesis of the antioxidant reduced glutathione, and decreases the iron content in SCD mouse spleen and liver tissues. Mechanistic studies suggest that simvastatin suppresses the expression of the critical histone methyltransferase enhancer of zeste homolog 2 to reduce both global and gene-specific histone H3 lysine 27 trimethylation. These chromatin structural changes promote the assembly of transcription complexes to fetal γ-globin and antioxidant gene regulatory regions in an antioxidant response element-dependent manner. In summary, our findings suggest that simvastatin activates fetal hemoglobin and antioxidant protein expression, modulates iron and cystine/reduced glutathione levels to improve the phenotype of SCD, and represents a therapeutic strategy for further development.